El Excentrico, 1978-07-05 - Garcia, Bert:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
July 5, 1978 [5 de julio de 1978]. Ano 29, No 7. Cover contains a portrait of model Leticia Graham, who was a Miss California National Teen-Ager pagent finalist.